2006
DOI: 10.1097/01.mao.0000226291.42165.22
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation of Multiple Genes in Vestibular Schwannoma

Abstract: Aberrant methylation of tumor-related genes may play a role in the development of vestibular schwannomas. Our results may provide useful clues to the development of prognostic assays for these tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…None of our patients showed repressed expression of the NF2 gene due to hypermethylation of the promoter region. Instead, methylation of other tumor-related genes may have played a role in the development of these vestibular schwannomas [22].…”
Section: Discussionmentioning
confidence: 99%
“…None of our patients showed repressed expression of the NF2 gene due to hypermethylation of the promoter region. Instead, methylation of other tumor-related genes may have played a role in the development of these vestibular schwannomas [22].…”
Section: Discussionmentioning
confidence: 99%
“…Presence of a modifier gene [72], methylation of the regulatory region [21, 22, 73], posttranscriptional alternative splicing, and differential polyadenylation of the NF2 gene [74] are proposed as possible causes. On the other hand, the NF2 gene promoter area is a region of DNA that facilitates transcription.…”
Section: Mutations Of the Nf2 Gene Dna Methylation And Hearing Lossmentioning
confidence: 99%
“…It has been claimed that DNA methylation represses transcription directly, by inhibiting the binding of transcription factors, or indirectly, by recruiting methyl-CpG-binding proteins. Hypermethylation of the promoter-associated CpG islands leads to transcriptional silencing and finally to epigenetic inactivation of tumor suppressor genes [21]. The DNA methylation of VS has not been fully studied.…”
Section: Mutations Of the Nf2 Gene Dna Methylation And Hearing Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated frequencies in genes known for their implication in diverse tumor types have been observed: THBS1 (30-36%), TP73 (19-27%), MGMT (16-20%), NF2 (18%), TIMP-3 (18%), RB1/p16INK4a pair (15%) and hMLH1 (21%) [63,64]. A further study has shown a correlation between clinical-radiological features and the aberrant hypermethylation of genic promoters in VS and significant associations of CASP8 with RASSF1A, and between the age of the patient and the tumor grade; also, a relation between the auditory loss and the methylation of TP73 has been observed, as well as an inverse correlation between the hypermethylation of RASSF1A and the clinical grade of tumor growth [65].…”
Section: Molecular Genetics Of Schwannomasmentioning
confidence: 92%